Wounding alters epidermal connexin expression and gap junction-mediated intercellular communication. - Goliger, J A (1995)
We show that connexin expression and in vivo patterns of communication were dramatically altered in response to epidermal wounding. Six hours after injury, Cx26 was up-regulated in the differentiated cells proximal to the wound, but was down-regulated in cells located at the wound edge. In contrast, Cx31.1 and Cx43 were down-regulated in cells both peripheral to and at the wounded edge. These patterns of altered connexin expression were detectable as early as 2 h after wounding and were most pronounced in 24-h old wounds. Increased expression of Cx26 was still evident in the hyperproliferative epidermis of 6-day old wounds. In vivo dye transfer experiments with Lucifer yellow and neurobiotin confirmed that junctional communication patterns were altered in ways consistent with changes in connexin expression. The data thus suggest that intercellular communication is intimately involved in regulating epidermal wound repair.